1999
DOI: 10.1038/sj.ejcn.1600841
|View full text |Cite
|
Sign up to set email alerts
|

Effect of consumption of a ready-to-eat breakfast cereal containing inulin on the intestinal milieu and blood lipids in healthy male volunteers

Abstract: Objective: To investigate the effect of a breakfast cereal containing inulin on blood lipids and colonic ecosystem in normolipidemic young men. Setting: Department of Food Science and Microbiology,University of Milan, Italy. Subjects: Twelve healthy male volunteers, age 23.3 AE 0.5 y, body mass index (BMI) 25.7 AE 1.2 kgam 2 (mean AE s.e.m.).Interventions: Subjects consumed daily, for three periods of four weeks, 50 g of a rice-based ready-to-eat cereal (placebo) and the same cereal containing 18% inulin (test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
99
2
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(111 citation statements)
references
References 24 publications
7
99
2
3
Order By: Relevance
“…Some data obtained in normo-or moderate hyperlipidaemic patients suggest that the daily consumption of about 10 g inulin for several weeks decreases triglyceridaemia and/or cholesterolaemia (Brighenti et al, 1999;Jackson et al, 1999). In our study, a decrease in triglyceridaemia due to OFS was observed in three patients out of seven (non significant).…”
Section: Resultscontrasting
confidence: 44%
“…Some data obtained in normo-or moderate hyperlipidaemic patients suggest that the daily consumption of about 10 g inulin for several weeks decreases triglyceridaemia and/or cholesterolaemia (Brighenti et al, 1999;Jackson et al, 1999). In our study, a decrease in triglyceridaemia due to OFS was observed in three patients out of seven (non significant).…”
Section: Resultscontrasting
confidence: 44%
“…13 Similarly, in another study involving eight healthy volunteers with a daily consumption of 10 g of inulin for 3 weeks, significant decrease in plasma triacylglycerides concentrations compared to the placebo was observed. 14 In another study by Brighenti et al,15 significant (P<0.05) reduction in plasma total cholesterol and triacylglycerols of twelve healthy rats was seen following 12-week consumption of 50 g of a rice-based ready-to-eat cereal containing 18% inulin. 15 According to the results of this study, B. coagulans did not contribute to any lipid profile changes after 30 days.…”
Section: Discussionmentioning
confidence: 99%
“…14 In another study by Brighenti et al,15 significant (P<0.05) reduction in plasma total cholesterol and triacylglycerols of twelve healthy rats was seen following 12-week consumption of 50 g of a rice-based ready-to-eat cereal containing 18% inulin. 15 According to the results of this study, B. coagulans did not contribute to any lipid profile changes after 30 days. Although many studies have demonstrated cholesterol-lowering effects of probiotics in both animals and humans, debatable results have also been reported concerning inability of a particular strain of probiotic bacteria to improve lipid profile.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the latter, most of the studies in this area compare the effects of exchanging sucrose or dextrins with fructo-oligosaccharides or inulin (Williams & Jackson, 2002). Effects that are seen in these cases may, along with a reduction of the amount of glycaemic CHO ingested, be due to the production of short-chain fatty acids during colonic fermentation (Brighenti et al 1999).…”
Section: Carbohydrate Basis For Glycaemic Index Determinationmentioning
confidence: 99%